Ukraine’s Industrial Policy: Intentions, Consequences, Prospects - GERASYMCHUK, Vasyl (University Scientific Notes, 2022)
Attention is focused on the loss of Ukraine’s positions in the group of industrially developed countries of the world and the transition to the group of agro-industrial, «economies with a developing industry», «modest innovators / weak positions». The need to consider the development of the country’s industry throughout the entire historical period (from the end of the 17th century) on a multifactorial basis for the formation of a balanced state industrial policy is noted. The cyclical nature of the dynamics of GDP and industrial output during 1990–2021 has been investigated under the influence of external and internal factors. For an objective assessment of the efficiency of production and consumption of industrial goods, it is proposed to widely use economic indicators not only in monetary terms, but also in physical units. The groundlessness of the sharp loss of scientific and industrial complexes in key industries and the reorientation of the industrial sphere to small and medium-sized businesses has been proved. This approach led to a significant decrease in the competitiveness of the products of the domestic manufacturer in the domestic and foreign markets. The author is concerned about the hasty privatization, dismantling of industrial complexes with the irreversible loss of millions of highly qualified specialists in the creative industries. The consequences of unjustified restructuring are disclosed on the example of VEB Carl Zeiss Jena (Germany) and enterprises of the domestic military-industrial complex. The disagreement between the proclaimed state target programs for industrial development (1996, 2003, 2008 and 2013) and their failure to be implemented in practice was sharply criticized. It is emphasized that the main reason for the unsatisfactory development of the industrial sphere is the lack of an effective organizational and economic mechanism for managing government programs. The formation of an industrially developed country and its economy is possible, first of all, if there is a Strategy and a Strategist following the example of L. Erhard (Germany), Deng Xiaoping (China) or L. Balcerowicz (Poland).
Keywords: deindustrialization of the economy; state industrial policy; restructuring; strategy; transformation processes